Robustness‐oriented distributed cooperative control for ac microgrids under complex environments. Issue 10 (1st July 2019) - Lai, Jingang; Lu, Xiaoqing; Dong, Zhengcheng; Tang, Ruo‐li; Li, Xin
Abstract : In this study, the power sharing problem of ac microgrids with massive penetration of photovoltaic generators (PVG) is addressed. A robust distributed cooperative control strategy is proposed to control multiple PVGs in ac microgrids under a complex environment (e.g. subject to transmission time delays and noise disturbances). The existing distributed control strategies have been commonly designed assuming ideal communication among PVGs. However, due to inherent communication delays and environmental noises, the real‐life practical channels are affected by time delay and additive noise leading each PVG to receive measurements of the states of its neighbours. Thus, the proposed distributed cooperative control strategy will achieve the accurate power sharing property among PVGs through a sparse communication network subject to time delays and noise disturbances. The theoretical concepts and necessary conditions for stability and robust performance of the proposed distributed cooperative control strategy are outlined by the Lyapunov functional method and stochastic differential equation theory. Furthermore, the proposed control strategy is fully implemented and thus satisfies the plug‐and‐play feature of the future smart grid. Simulation results on an islanded microgrid test system are provided to reveal the effectiveness of the proposed control method to provide accurate proportional power sharing in the MATLAB/SimPowerSystems Toolbox.